INTEGRATED GEOPHYSICAL AND GEOTECHNICAL ANALYSIS TO SUBSURFACE LITHOLOGY OVERVIEW AT ITERA DORMITORY SITE, LAMPUNG, INDONESIA - Santoso, Nono Agus; Irwanto, Prastowo Adhi; Syuhada, Syahidus (Universitas Mataram, 2025)
The Student Dormitory is a gathering place for most new students at ITERA. For disaster mitigation, it is necessary to conduct geophysical and geotechnical surveys. Geophysical and geotechnical surveys are conducted to describe the subsurface lithology. The purpose of this study is to identify the subsurface of the Dormitory building so that it can be determined which buildings have the potential for geological hazards. The methods used are geomagnetic, geoelectric and geotechnical methods. The results obtained are that High and low magnetic anomalies are related to the thickness of the lithology. This is also justified by the results of geoelectric using resistivity cross-sections. The thickness of this lithology is related to the level of building security. TB4 has the highest security based on magnetic and geoelectric data. Meanwhile, TB1 has the lowest security based on subsurface conditions.